2022
DOI: 10.1021/jacs.2c03088
|View full text |Cite
|
Sign up to set email alerts
|

Unraveling Molecular Fingerprints of Catalytic Sulfur Poisoning at the Nanometer Scale with Near-Field Infrared Spectroscopy

Abstract: Fundamental understanding of catalytic deactivation phenomena such as sulfur poisoning occurring on metal/metal-oxide interfaces is essential for the development of high-performance heterogeneous catalysts with extended lifetimes. Unambiguous identification of catalytic poisoning species requires experimental methods simultaneously delivering accurate information regarding adsorption sites and adsorption geometries of adsorbates with nanometer-scale spatial resolution, as well as their detailed chemical struct… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
10
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 13 publications
(10 citation statements)
references
References 81 publications
0
10
0
Order By: Relevance
“…Pd/zeolites are enigmatic model systems with unusual chemistry and relevance in the industry. , Entrapped metal ions or clusters with steric constraints by the zeolite structure carry strong potential for various catalytic reactions. , The unusual state of the “naked” di/polyvalent metal ions in zeolites has recently been identified, providing a framework for understanding high coordinative unsaturation and reactivity. These cations can be reduced to metallic Pd or Pt under certain reductive conditions, leading to rich chemistry and a smear of species present both in the micropores (smaller species) and outside zeolitic micropores (nanoparticles). These metals are typically used for oxidative reactions of carbon monoxide, nitric oxide, and hydrocarbons. Carbon monoxide (CO) is a highly toxic pollutant gas that is produced by incomplete combustion of fossil fuels and is a major contributor to the worsening air quality.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Pd/zeolites are enigmatic model systems with unusual chemistry and relevance in the industry. , Entrapped metal ions or clusters with steric constraints by the zeolite structure carry strong potential for various catalytic reactions. , The unusual state of the “naked” di/polyvalent metal ions in zeolites has recently been identified, providing a framework for understanding high coordinative unsaturation and reactivity. These cations can be reduced to metallic Pd or Pt under certain reductive conditions, leading to rich chemistry and a smear of species present both in the micropores (smaller species) and outside zeolitic micropores (nanoparticles). These metals are typically used for oxidative reactions of carbon monoxide, nitric oxide, and hydrocarbons. Carbon monoxide (CO) is a highly toxic pollutant gas that is produced by incomplete combustion of fossil fuels and is a major contributor to the worsening air quality.…”
Section: Introductionmentioning
confidence: 99%
“…Carbon monoxide (CO) is a highly toxic pollutant gas that is produced by incomplete combustion of fossil fuels and is a major contributor to the worsening air quality. Palladium (Pd) catalysts have been used for the oxidation of CO in various industrial applications due to their high activity. However, the use of Pd catalysts can be expensive and may also suffer from issues such as deactivation and poisoning . It is well known about Pd nanoparticles that once CO adsorbs on them, O 2 dissociation sites are blocked (due to a higher affinity of CO for Pd) and there is no activity in CO oxidation at low temperature. , Only when CO desorption begins to occur do the nanoparticles start catalyzing CO oxidation.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the abovementioned facts, the concentrations and ratios of cysteamine have a signicant impact on the quantity of oxTMB in the system. As such, different ratios (25,50,75, and 100 mL) of 200 mM cysteamine were employed to assess the inhibition of the catalytic activity of the pAuNP-Tablet. It was observed that the maximum inhibition was achieved using 100 mL of cysteamine.…”
Section: Optimization Of the Cysteamine Assay Using The Paunp-tablet ...mentioning
confidence: 99%
“…It is therefore clear that the state of the surface plays a critical role when defining the barriers of the rate limiting step, which on a clean Pd surface for hydrogen absorption is the step from the surface to the first subsurface site and associative desorption of H 2 from the surface for the reverse process . However, it has also been shown that surface contaminants such as carbon monoxide (CO) and sulfuric or sulfidic compounds (e.g., SO 2 and H 2 S), as well as surfactant molecules used for colloidal synthesis of Pd nanocrystals , distinctly affect the rate of hydrogen sorption and the corresponding energetics. , At the same time, surface contamination is unavoidable upon exposure to ambient conditions or in colloidal Pd nanoparticle synthesis due to the multiple key roles of surfactants/capping agents, such as solubilizing the initial reagents, directing shape-selected particle growth, and preventing nanoparticle aggregation in suspension …”
Section: Introductionmentioning
confidence: 99%